Communication Strategy of Health Cadres in Stunting Prevention - Nasywa Salsabila; Nur Aliya Natasyah; Farida Nurul Rakhmawati; Qurrotin A’yun (Literasi Nusantara, 2026)
This study aims to analyze the communication strategies employed by health cadres in stunting prevention in Pejagan Village. This study used a qualitative, descriptive approach to gain a deeper understanding of the communication process between health cadres and the community. Data were collected through interviews, observation, and documentation. The results indicate that health cadres implemented various communication strategies, such as outreach at integrated health posts (Posyandu), interpersonal communication, and door-to-door visits. Furthermore, the use of communication media such as leaflets, KIA (Child Health Information) books, and social media contributed to the dissemination of information to the community. However, challenges remain, including low public awareness of the importance of a healthy lifestyle and limited data on stunted toddlers. Therefore, a more adaptive and sustainable communication strategy is needed to ensure a more effective stunting prevention program.